Geohazard mapping and mitigations along the road corridor Gasera–Indeto, Southeast Ethiopia - Chalachew Tesfa (Environmental and Sustainability Indicators)
The study area is one of the biggest gorges in southeast Ethiopia formed by the Wabe Shebelle river. The road was constructed to connect Gasera to Indeto. The study aimed to map and gives some mitigation strategies for geohazards along the road corridor in Southeast Ethiopia using a GIS with AHP & FR technique within the 3 km buffer zones along the road corridor. The study included field investigations and inventorying, characterization of geological situations, assessments of the hydrogeological conditions, and identification of slope instability variables. A GIS technique was used to map an LSM with the combination of two models (AHP and FR). The study used eight factors: slope, aspect, lithology, rainfall, altitude, road proximity, river proximity, and land use/cover. The results of the study revealed that LSZ maps performed using FR and AHP were 64.5 % and 69 % and-the inventory shows high and very high LSZ respectively. Rockfalls, debris/earth slides, and rockslides are commonly observed landslides in the area. Based on the analysis lithology (basaltic and limestone formations) showed the highest contributions for landslide in the area. Slope and aspects show the most frequent landslide hazards in >40, 30–40°, and east, and northeast respectively. Generally, the study found that lithology, slope, and aspect were the main factors contributing to slope instability in the study area. The produced landslide susceptibility map is very important for urban planners, agricultural studies, environmentalists, and future landslide hazardous prevention and mitigation strategies.